Academic stress and stress management strategies among undergraduate nursing students - Moussa Sarr; Ousmane Diallo (Malahayati International Journal of Nursing and Health Science, 2026)
Background: In order to handle their academic obligations and reduce stress, students needed to have effective coping techniques. In order to plan interventions, nurse educators are suggested to assess the stress level of the nursing program because various nursing students have varying amounts of stress and coping mechanisms. Purpose: To investigate the variations in nursing undergraduates' academic stress and coping mechanisms. Method: Undergraduate nursing students made up the population of the descriptive study, which employed a cross-sectional approach. Census sampling was used, and the stress coping style survey and the stress related to school questionnaire were the instruments used to gather data. For inferential analysis, ANOVA was used, and the results were presented as means and standard deviations. Results: Age group differences in peer stress were significant (p = 0.004). Male respondents have lower mean academic stress than female respondents, with the exception of peer stress. There was a significant gender difference in the mean academic stress for peers and teachers (p = 0.04 and 0.02, respectively). Academic stress ranges from 300 to 400 on average, with the exception of group study. Active problem dealing had the highest mean score across all age groups. There is no appreciable difference in stress coping mechanisms among all the variables. Male respondents have a greater mean stress coping style than female respondents when it comes to active emotional coping and active issue coping, with significant differences of p = 0.011 and 0.045, respectively. The 500-level respondents have the highest mean stress coping style across all metrics when compared to respondents from other levels. Conclusion: When creating therapies to lessen academic stress among undergraduate nursing students, lower age groups should be taken into consideration. Female students require more attention than male students. Students at the 300 and 400 levels should be given more attention than those at lower levels. Additionally, students should be taught a variety of coping strategies, where to apply them, and the consequences of each, regardless of their age, gender, or academic standing.